Development of an integrated internal managament system (IICS) model and an efficiency measurement algorithm - Tomov, Kristian (Yearbook Telecommunications, 2014)
The issue of creating and implementing integrated internal management systems is very topical (IICS) for the governance of telecommunications and information technology structures . The use of an IICS for the corporate governance should be considered, as this would be an essential solution to the open questions on the efficient management especially in international companies. In the practice of research, analysis and audit of IICS many practical approaches based on international applied standards are used. This paper proposes a IICS model, a methodology and an algorithm for the evaluation of its operating efficiency.